Socio-Economic Analysis of IoT-Based Automatic Fish Feeding Technology and Renewable Energy Implementation in Milkfish Cultivation in Cilacap Regency (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2025)
Cilacap Regency, located in Central Java, has growing fisheries potential, particularly known for its aquaculture activities such as milkfish farming. However, the fish feeding system is still mostly done manually, which affects productivity and efficiency. This research aims to develop and analyze environmentally friendly fish feeding technology to increase the income and welfare of the milkfish farming community. The study involves designing a Tosfeed using a tool design modeller and utilizing solar panels as the main energy source, ensuring sustainability and independence from electricity. Stability and structural analyses showed that the Tosfeed is sturdy and reliable when used in aquaculture ponds. Furthermore, economic feasibility analysis revealed a production cost of IDR 11,795,375 with a payback period of 11 months through a bank loan scheme. This scheme was chosen because it has the highest IRR (23.10%) compared to other options, thus accelerating the profit farmers can earn. Tosfeed effectively automates fish feeding, improving efficiency and productivity for aquaculture businesses. This innovation is expected to empower fish farming MSMEs by providing a reliable, environmentally friendly, and cost-effective solution for sustainable aquaculture.